2014
DOI: 10.1155/2014/957076
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Expression in the Porcine Ovary during the Oestrous Cycle and Its Effect on Ovarian Steroidogenesis

Abstract: Adiponectin is an adipose-secreted hormone that regulates energy homeostasis and is also involved in the control of the reproductive system. The goal of the present study was to investigate changes in adiponectin gene and protein expression in porcine ovarian structures during the oestrous cycle and to examine the effects of in vitro administration of adiponectin on basal and gonadotrophin- and/or insulin-induced secretion of ovarian steroid hormones. Both gene and protein expression of adiponectin were enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 46 publications
(62 reference statements)
6
42
0
1
Order By: Relevance
“…Experimental data supporting a direct effect of adiponectin on ovarian function is inconsistent, and research has mainly been performed in vitro (22). In line with our observation of high estradiol levels in APNtg mice, another study has found that high doses of adiponectin stimulates basal secretion of estradiol from porcine granulosa cells (56). In this same study, researchers observed decreases in testosterone secretion by adiponectin exposure.…”
Section: Discussionsupporting
confidence: 74%
“…Experimental data supporting a direct effect of adiponectin on ovarian function is inconsistent, and research has mainly been performed in vitro (22). In line with our observation of high estradiol levels in APNtg mice, another study has found that high doses of adiponectin stimulates basal secretion of estradiol from porcine granulosa cells (56). In this same study, researchers observed decreases in testosterone secretion by adiponectin exposure.…”
Section: Discussionsupporting
confidence: 74%
“…Ledoux et al (2006) observed higher levels of prostaglandin-endoperoxide synthase 2 (PTGS2), prostaglandin E synthase (PTGES), and vascular endothelial growth factor (VEGF) gene expression in granulosa cells primed with adiponectin, an increase in the expression of the steroidogenic acute regulatory protein (StAR) gene, and a decrease in the expression of the P450 aromatase gene in granulosa cells derived from prepubertal gilts. Adiponectin was also found to affect the basal and stimulated secretion of steroid hormones, i.e., progesterone, estradiol, androstenedione, and testosterone, by ovarian cells of mature gilts (Maleszka et al 2014a). These results undoubtedly confirm the involvement of adiponectin in the functioning of the reproductive system.…”
Section: Introductionsupporting
confidence: 58%
“…The mid-luteal phase is characterized by the highest activity of CL, an endocrine gland secreting estrogens and, most of all, significant amounts of progesterone. Adiponectin had an inhibitory effect on in vitro secretion of progesterone by porcine luteal cells on days 10 to 12 of the estrous cycle (Maleszka et al 2014a). The effect of adiponectin on ovarian basal progesterone secretion was also suggested in studies on cows, rats, and humans (Chabrolle et al 2009;Mailard et al 2010;Lagaly et al 2008).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations